2017
DOI: 10.1371/journal.pone.0177069
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular glutamate transporters play a role in neuronal differentiation of cultured SVZ-derived neural precursor cells

Abstract: The role of glutamate in the regulation of neurogenesis is well-established, but the role of vesicular glutamate transporters (VGLUTs) and excitatory amino acid transporters (EAATs) in controlling adult neurogenesis is unknown. Here we investigated the implication of VGLUTs in the differentiation of subventricular zone (SVZ)-derived neural precursor cells (NPCs). Our results show that NPCs express VGLUT1-3 and EAAT1-3 both at the mRNA and protein level. Their expression increases during differentiation closely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Gliotransmission can be achieved by vesicular‐dependent and independent mechanisms (Bazargani & Attwell, ), involving regulated exocytosis (Araque et al, ), and connexin/pannexin hemichannels (Bennett et al, ). Following the intracellular loading of astrocytes with Evans blue (5 μM), which blocks both the vesicular glutamate transporter (VGLUT) function (Eriksen et al, ; Goh et al, ; Sanchez‐Mendoza et al, ), and the nucleotide transporters (VNUTs) that actively accumulate ATP into vesicles (Geisler et al, ; Oya et al, ; Sakamoto et al, ), light stimulation failed to induce astrocyte‐mediated increase of SIC frequency (Figure e; 0.68 ± 0.31; n = 8; p = 0.677), as well as blocked the transient synaptic potentiation (Figure f, 99.96 ± 7.24%; n = 8 neurons; p = 0.996). Conversely, the blockage of connexin‐hemichannels and gap junctions by bath application of the connexin 43 mimetic peptide Gap26 (100 μM; Karpuk, Burkovetskaya, Fritz, Angle, & Kielian, ; Roux et al, ) did not prevent both the increase of SIC frequency (Figure (e), 1.95 ± 0.52; n = 8; p = 0.016), and synaptic potentiation evoked by melanopsin‐astrocyte stimulation (Figure f, 126.33 ± 14.73%; n = 8; p = 0.010).…”
Section: Resultsmentioning
confidence: 99%
“…Gliotransmission can be achieved by vesicular‐dependent and independent mechanisms (Bazargani & Attwell, ), involving regulated exocytosis (Araque et al, ), and connexin/pannexin hemichannels (Bennett et al, ). Following the intracellular loading of astrocytes with Evans blue (5 μM), which blocks both the vesicular glutamate transporter (VGLUT) function (Eriksen et al, ; Goh et al, ; Sanchez‐Mendoza et al, ), and the nucleotide transporters (VNUTs) that actively accumulate ATP into vesicles (Geisler et al, ; Oya et al, ; Sakamoto et al, ), light stimulation failed to induce astrocyte‐mediated increase of SIC frequency (Figure e; 0.68 ± 0.31; n = 8; p = 0.677), as well as blocked the transient synaptic potentiation (Figure f, 99.96 ± 7.24%; n = 8 neurons; p = 0.996). Conversely, the blockage of connexin‐hemichannels and gap junctions by bath application of the connexin 43 mimetic peptide Gap26 (100 μM; Karpuk, Burkovetskaya, Fritz, Angle, & Kielian, ; Roux et al, ) did not prevent both the increase of SIC frequency (Figure (e), 1.95 ± 0.52; n = 8; p = 0.016), and synaptic potentiation evoked by melanopsin‐astrocyte stimulation (Figure f, 126.33 ± 14.73%; n = 8; p = 0.010).…”
Section: Resultsmentioning
confidence: 99%
“…3f ). Thus, while inhibition of vesicular glutamate transporters (VGLUTs) promotes neuronal differentiation and migration of NPCs [ 32 ], we observed that miR-146a overexpression caused downregulation of the vesicular glutamate transporter gene SLC17A8 . Similarly, RNA-Seq data revealed downregulation of the LIN28B gene; the RNA binding protein LIN28B plays essential functions in neuroblast proliferation by maintaining neural progenitors in an early state [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have provided evidence that DM alters neurotransmitter systems, such as γ-aminobutyric acid (GABA) and glutamate transporters. GABA and glutamate are the principal inhibitory and excitatory neurotransmitters, respectively, in mammalian central nervous systems, and their transporters modulate adult neurogenesis [ 135 , 136 , 137 , 138 , 139 ]. The expressions of GABA transporters (GATs), excitatory amino acid transporters, and vesicular glutamate transporter is decreased in the OB of STZ-induced diabetic as compared to healthy rats [ 133 ].…”
Section: Alteration Of Stem Cell Function In Diabetesmentioning
confidence: 99%